La reconducción estratégica de Al-Qaeda: ¿del liderazgo de Osama bin Laden a la dimensión masiva-popular? (2012)
This article seeks to establish the relationship of global strategic variables of Al-Qaeda with religious ideology; political Islam; trying to incorporate a cross section and total phenomenon. It argues that the link lies in the expansion strategy and top-down decentralization created by the central base of Al-Qaeda; where regional networks have some autonomy but are determined by the central leadership and his adaptation of the Islamist ideology to an internationalist shed; revolutionary and violent organization